The role of mindfulness on the relationship between daily micro-events and daily gratitude: A within-person analysis - Junça Silva, A.; Mosteo, L.; Lopes, R. R. (Personality and Individual Differences, 2023)
This study is based on the affective events theory and aimed to investigate the situational predictors for mindfulness-related differences in daily affect and gratitude. We tested a mediated moderation model in which daily micro-events (daily hassles and uplifts) were related to affect and gratitude at the within-person level. We also tested a cross-level interaction of mindfulness on the relationship between daily micro-events and gratitude and between daily micro-events and affect. A total of 101 participants participated in a 10-day diary study (n = 1010). Multilevel modeling showed that, at the person-level of analysis, daily micro-events were significantly related to daily affect, and in turn, to daily gratitude. At the within-level of analysis mindfulness moderated the link between daily micro-events and daily gratitude and between daily micro-events and daily affect, such that it become stronger for individuals who scored higher on mindfulness. These findings make relevant theoretical contributions to understanding the power of mindfulness for daily affective dynamics. These results also expand knowledge on within-person processes that explain daily affect and gratitude, in addition to more traditional between-person factors. In sum, the present research demonstrates that being mindful may improve, not only positive affect, but also gratitude.